A case report of primary hepatic neuroendocrine tumour (VIPoma) of liver - Chotai, Tulsi J.; Sindhu, R. S.; J., Nirmal (International Surgery Journal, 2025)
Rare cancers that start in the cells of the neuroendocrine system are called neuroendocrine tumors (NETs). The gastrointestinal and respiratory systems are among the organs where they are most frequently detected. Due to their rarity and sluggish growth rate, primary hepatic neuroendocrine tumors (PHNETs) are frequently difficult to identify until the disease has advanced to a later stage. A case of 22-year-old male patient with history of chronic diarrhoea for two years, large volume (700–1000 ml/day), watery, yellow colour, frequency of 6-7 times/day, not associated with abdomen pain or blood and mucus in stools. He had lost 9 kg weight over 2 years with preserved appetite. He was evaluated in multiple hospitals as infective diarrhoea or irritable bowel syndrome (IBS). Routine investigations revealed dehydration related acute kidney injury, hypokalaemia and compensated normal anion gap acidosis. Ultrasound and magnetic resonance imaging (MRI) identified a liver lesion suggestive of hemangioma. PHNETs are uncommon liver tumors that can be difficult to differentiate from other liver tumor types since they frequently exhibit vague symptoms. For PHNETs, hepatectomy is the recommended course of treatment. However, different strategies need to be taken into account when there are several intrahepatic lesions or when surgery is not an appropriate treatment for vascular invasion.